Use of FTIR, FT-Raman and 13C-NMR spectroscopy for identification of some seaweed phycocolloids - Pereira, Leonel (2003)
Many seaweeds produce phycocolloids, stored in the cell wall. Members of the Rhodophyceae produce polysaccharides the main components of which are galactose (galactans)--agar and carrageenan. In addition, alginic acid is extracted from members of the Phaeophyceae. This is a binary polyuronide made up of mannuronic acid and guluronic acid. The wide uses of these phycocolloids are based on their gelling, viscosifying and emulsifying properties, which generate an increasing commercial and scientific interest. In this work, the FTIR and FT-RAMAN spectra of carrageenan and agar, obtained by alkaline extraction from different seaweeds (e.g. Mastocarpus stellatus, Chondrus crispus, Calliblepharis jubata, Chondracanthus acicularis, Chondracanthus teedei and Gracilaria gracilis), were recorded in order to identify the type of phycocolloid produced. The spectra of commercial carrageenan, alginic acid and agar samples (SIGMA and TAAB laboratories) were used as references. Special emphasis was given to the 500-1500 cm-1 region, which presents several vibrational modes, sensitive to the type of polysaccharide and to the type of glycosidic linkage. The FT-Raman spectra present a higher resolution than FTIR spectra, this allowing the identification of a larger number of characteristic bands. In some cases, phycocolloids can be identified by FT-Raman spectroscopy alone.